2009
DOI: 10.3844/ajabssp.2009.224.229
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Protects Nitrate Reductase Activity, Growth and Proline in Amaranth and Tomato Plants during Water Deficit

Abstract: Problem statement: Seedlings of Amaranthus hybridus cv. NHAC-3 (large green, amaranth) and Lycopersicum esculentum cv. Roma (tomato) were subjected to 7 days water stress at Early Vegetative (EV), Late Vegetative (LV), Early Flowering (EF) and Late Flowering (LF) stages of growth to study the impact on leaf water potential (ψ w ), Nitrate Reductase Activity (NRA), growth (plant height, shoot and root biomass) and proline content of both plants. Approach: Two concentrations of salicylic acid (1 and 3 mM SA) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 18 publications
3
28
0
4
Order By: Relevance
“…Therefore, early detection of water-deficit stress is important for irrigation management and could serve as a selection mechanism for drought tolerance. Studies on other crops have indicated that leaf RWC and/or proline content are useful indicators for early detecting plant water-deficit stress (Bates et al, 1973;Aspinall and Paleg, 1981;Ilahi and Dorffling, 1982;Levy, 1983;Claussen, 2005;Gonzalez et al, 2008;Umebese et al, 2009;Paknejad et al, 2009). Ilahi and Dorffling (1982) investigated changes in proline of four maize varieties differing in drought resistance during a prolonged water stress period and found that proline levels increased continuously during the stress period in all the four varieties, but to different amounts with higher level of proline in the drought-susceptible varieties than the drought-resistant varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early detection of water-deficit stress is important for irrigation management and could serve as a selection mechanism for drought tolerance. Studies on other crops have indicated that leaf RWC and/or proline content are useful indicators for early detecting plant water-deficit stress (Bates et al, 1973;Aspinall and Paleg, 1981;Ilahi and Dorffling, 1982;Levy, 1983;Claussen, 2005;Gonzalez et al, 2008;Umebese et al, 2009;Paknejad et al, 2009). Ilahi and Dorffling (1982) investigated changes in proline of four maize varieties differing in drought resistance during a prolonged water stress period and found that proline levels increased continuously during the stress period in all the four varieties, but to different amounts with higher level of proline in the drought-susceptible varieties than the drought-resistant varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Proline is generally considered as a good indicator of environmental stress in tomato (Clausen, 2005) and there are many reports describing an increase in Pro contents as a response to water or salt stress in this species (Babu et al, 2012;Ghorbanli et al, 2013;Giannakoula and Ilias, 2013;Inal, 2002;Handa et al, 1986;Nahar and Gretzmacher, 2002;Umebese et al, 2009;Yokas et al, 2008), although it should be mentioned that data specific for cherry tomatoes are rather scarce (Maggio et al, 2007;Rosales et al, 2007). What is not so clear is the possible contribution of Pro accumulation to the (relative) resistance of tomato to salinity.…”
Section: Malondialdehydementioning
confidence: 99%
“…In a previous work, we found that wheat seedlings treated with coumarin exhibited a significant increase in phenolic, flavonoids and proline . Similarly, salicylic acid induced a two-fold increase in proline content at the vegetative stage of tomato plants (Umebese et al, 2009). In accordance with our results, chickpea and cucumber seedlings treated with ellagic and ferulic acids has markedly enhanced proline accumulation (Abu El-Soud et al, 2013 andLi et al, 2013) Cell damage occurs in consequent of adverse environmental stimuli which disrupts the normal homeostasis of affected cells.…”
Section: Discussionmentioning
confidence: 99%